2020
DOI: 10.1039/d0ma00448k
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and sulfur co-doped fluorescent carbon dots for the trapping of Hg(ii) ions from water

Abstract: An unsophisticated, reliable and ultrasensitive fluorescent sensor motif based on Carbon Dots (CDs) co-doped with nitrogen and sulfur atoms has been fabricated using calix[4]arene and benzothiazole moieties for the recognitionof...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Furthermore, the strength of the interaction between FeCl 3 and Bf was calculated using the Benesi–Hildebrand relation (1) and was found to be 0.632 × 10 5 M –1 , indicating excellent binding affinity of the metal salt toward Bf, as shown in Figure S6 log false( A A o false) false( A f A o false) = log false[ F e false] + log K b A 0 , A, and A f are the absorption values in the absence of ferric ion, at the intermediate level of ferric ion concentration, and at the saturation of the ferric ion, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the strength of the interaction between FeCl 3 and Bf was calculated using the Benesi–Hildebrand relation (1) and was found to be 0.632 × 10 5 M –1 , indicating excellent binding affinity of the metal salt toward Bf, as shown in Figure S6 log false( A A o false) false( A f A o false) = log false[ F e false] + log K b A 0 , A, and A f are the absorption values in the absence of ferric ion, at the intermediate level of ferric ion concentration, and at the saturation of the ferric ion, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the strength of the interaction between FeCl 3 and Bf was calculated using the Benesi−Hildebrand relation (1) and was found to be 0.632 × 10 5 M −1 , indicating excellent binding affinity of the metal salt toward Bf, as shown in Figure S6. 32…”
Section: Figure 5 (A)mentioning
confidence: 99%
“…UV–vis spectra were observed from 200 to 800 nm for all the samples. A calibration plot was obtained with known concentrations of the VOC, which were analyzed spectroscopically. , Linear regression coefficients of 0.98986, 0.98345, and 0.99944 were observed for benzofuran, benzoic acid, and dibenzothiophene, respectively. The concentration of the remaining VOC in the solution after binding was calculated using these calibration plots, and the percentage of VOC adsorbed per 10 mg of the biochar was then calculated.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that the fluorescence intensity of the as‐synthesized CDs can be absolutely quenched in the presence of Hg 2+ ions because of the electron/energy transfer process between the surface functional groups of the CDs and soft closed‐shell Hg 2+ ions. The proposed nanosensor can detect Hg 2+ ions in aqueous media with a detection limit of about 7.89 nM with high selectivity, sensitivity, and relatively low background interference even in complex media [59] …”
Section: Sensing Of Specific Ions Containing Metalsmentioning
confidence: 99%